Influence of oxygen addition on the oxidation resistance of TiAlN. (February 2023) - Wang, Song; Zhang, Jie; Kong, Yi; Chen, Li; Du, Yong
Abstract: Here, we explore the effect of O-addition on the oxidation resistance of TiAlN coatings by experimental and theoretical methods. Due to the retarded transformation of anatase to rutile TiO2, Ti0.41 Al0.59 (O0.08 N0.92 )1.02 with the raised oxidation onset temperature and slow oxidation process reveals improved oxidation resistance than Ti0.42 Al0.58 N0.95 . Further ab initio calculations attribute the optimization to the preferential adsorption of oxygen to form the protective Al2 O3 phase and suppressed formation of metastable a-TiO2 phase in the initial stage of oxidation. However, both experimental and calculated results reveal that further increasing oxygen content to Ti0.41 Al0.59 (O0.12 N0.88 )1.06 shows the rapid transformation of TiO2 accompanied with the cracking of the protective Al-oxide rich top-layer, which tremendously deteriorates the oxidation resistance. After oxidation at 800 °C for 30 h, Ti0.42 Al0.58 N0.95, Ti0.41 Al0.59 (O0.08 N0.92 )1.02 and Ti0.41 Al0.59 (O0.12 N0.88 )1.06 coatings present oxide layers of ∼953, ∼640 and ∼971 nm, respectively. Graphical abstract: Image, graphical abstract